Cultura financiera de los trabajadores de la clínica Sersalud EIRL, Iquitos - periodo 2022 - Tuesta Tafur, Jhonatan (2023)
The present research work entitled "Financial Culture in Workers of the SERSALUD EIRL Clinic, Iquitos - period 2022" was carried out with the objective of determining the level of Financial Culture in the workers of the SERSALUD EIRL Clinic, Iquitos - period 2022 , for which a descriptive investigation was chosen, of a non-experimental design, where 30 company workers who voluntarily decided to participate in this research work were taken as the study population, to whom the technique was applied. of the survey and as an instrument the questionnaire; According to the analysis of the results, it was determined that the workers of the SERSALUD EIRL Clinic, Iquitos - period - 2022 have a medium level of knowledge and tax awareness since 80% of the workers have a medium level of financial knowledge, a 10% have a high level of financial knowledge and 10% have a low level of financial knowledge, and in terms of knowledge about financial tools or products, 70% of workers have a medium level, 10% have a high level and 20% have a low level, it is concluded that the workers have a medium level of financial literacy.